If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9f + 6g + -4f + -2g + 2 = 0 Reorder the terms: 2 + 9f + -4f + 6g + -2g = 0 Combine like terms: 9f + -4f = 5f 2 + 5f + 6g + -2g = 0 Combine like terms: 6g + -2g = 4g 2 + 5f + 4g = 0 Solving 2 + 5f + 4g = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 5f + -2 + 4g = 0 + -2 Reorder the terms: 2 + -2 + 5f + 4g = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5f + 4g = 0 + -2 5f + 4g = 0 + -2 Combine like terms: 0 + -2 = -2 5f + 4g = -2 Add '-4g' to each side of the equation. 5f + 4g + -4g = -2 + -4g Combine like terms: 4g + -4g = 0 5f + 0 = -2 + -4g 5f = -2 + -4g Divide each side by '5'. f = -0.4 + -0.8g Simplifying f = -0.4 + -0.8g
| 16x^2+8x+2=10 | | 5(x+6)=3(x-5) | | 3y+6=-18 | | -0.375h=-12 | | 36x+159= | | 5x-15=30+2 | | 2x+1y=78 | | -2.6h=-12 | | 8(x+4)=6(x-2) | | (5x+4)(3x+2)=(7x-1)(3x-5)+60x-51 | | 2(5+w)=94-w | | 1=7-3x | | 7p=7(4p+9) | | (5+2w)+w=94 | | x=(-8) | | 5m-2m+4m-6m= | | 4.7x-39=2.3x+9 | | 6(6x+6)=36x+36 | | 6ab-3ba= | | 5x^2-36x-108=0 | | 14k-70=42 | | 4x^2-10x-288=x^2-22x | | 2(x)+x=180-63 | | 2k-10=-42 | | x+(3x-10)=90 | | (7*3)-n=9 | | 9/5•42 | | Logb(6x^4)-7logb(x)=0 | | 8a^2-98=0 | | 4÷102/3 | | 4/3(-12=160 | | -5(7-6b)=-6b-35 |